THE ROLE OF PHARMACEUTICAL HEALTH EDUCATION IN HIV PREVENTION: AN INTEGRATIVE REVIEW ON ACCESS AND ADHERENCE TO PREP AND PEP (REMUNOM, 2025)
The human immunodeficiency virus (HIV) remains one of the major global public health challenges. Strategies such as pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP) play a key role in prevention, especially among vulnerable populations. In this context, pharmaceutical health education stands out as an essential tool to promote access, adherence, and correct use of these prophylaxis strategies. This study aims to analyze, through an integrative review, the impact of the pharmacist's role in promoting health education focused on HIV prevention, emphasizing the strengthening of adherence to PrEP and PEP. The study investigated barriers, facilitators, and successful practices related to the pharmacist’s work in counseling and monitoring users. The results show that the presence of a qualified pharmacist significantly contributes to expanding access and increasing the effectiveness of prevention strategies, highlighting the importance of health education in the fight against HIV.